2009
DOI: 10.1242/jcs.048124
|View full text |Cite
|
Sign up to set email alerts
|

The β- and γ-isoforms of type I PIP5K regulate distinct stages of Ca2+ signaling in mast cells

Abstract: Crosslinking of IgE receptors by antigen initiates Ca2+ mobilization in mast cells by activating phospholipase-Cγ-mediated hydrolysis of phosphatidylinositol-4,5-bisphosphate [PtdIns(4,5)P2]. The resulting inositol 1,4,5-trisphosphate-mediated Ca2+ release from the endoplasmic reticulum (ER) activates store-operated Ca2+ entry, which is necessary for exocytotic release of inflammatory mediators. To investigate roles for PtdIns(4,5)P2-synthesizing isozymes of the type I phosphatidylinositol 4-phosphate 5-kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 39 publications
(52 reference statements)
1
40
1
Order By: Relevance
“…The disassociation of PI(4)P5K I g from prominin-1 is not caused by a possible diffusion of prominin-1, because Western blots showed that the majority of prominin-1 was still located in microvilli (Figure 7B). Because PI(4)P5K I g is a major kinase that phosphorylates PI(4)P at five positions to produce PI(4,5)P 2 , 32 these data indicate that lovastatin may regulate ROMK1 channels by inducing PI(4)P5K I g diffusion into planar regions to initiate PI (4,5)P 2 synthesis near the channel.…”
Section: Lovastatin Induces Diffusion Of Pi(4)p5k I G Into Planar Regmentioning
confidence: 81%
“…The disassociation of PI(4)P5K I g from prominin-1 is not caused by a possible diffusion of prominin-1, because Western blots showed that the majority of prominin-1 was still located in microvilli (Figure 7B). Because PI(4)P5K I g is a major kinase that phosphorylates PI(4)P at five positions to produce PI(4,5)P 2 , 32 these data indicate that lovastatin may regulate ROMK1 channels by inducing PI(4)P5K I g diffusion into planar regions to initiate PI (4,5)P 2 synthesis near the channel.…”
Section: Lovastatin Induces Diffusion Of Pi(4)p5k I G Into Planar Regmentioning
confidence: 81%
“…We previously demonstrated that different isoforms of type I phosphatidylinositol 4-phosphate 5-kinase (PIP5KI), namely PIP5KI and PIP5KI, synthesize functionally distinguishable pools of PtdIns(4,5)P 2 that have distinct roles in SOCE and inositol trisphosphate (Ins(1,4,5)P 3 ) generation, respectively (Vasudevan et al, 2009). In the present study we characterize a membrane structural basis for distinctive pools of PtdIns(4,5)P 2 .…”
Section: Introductionmentioning
confidence: 81%
“…PLC cleaves PtdIns(4,5)P 2 into DAG and IP 3 ; the latter binds to receptors on the endoplasmic reticulum and stimulates the release of Ca 2+ (Berridge, 2009). Knockdown or genetic ablation of PIPKIc results in diminished intracellular [Ca 2+ ] changes in HeLa cells, mast cells and mesenchymal stem cells (Wang et al, 2004;Vasudevan et al, 2009;Yu et al, 2011), implicating PIPKIc as the source of this pool of PtdIns(4,5)P 2 . Cationic amino acid transporter (CAT-2) knockout mice provide indirect in vivo evidence for PIPKIc involvement in Ca 2+ signaling in smooth muscle (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A role for PIPKIc in agonist-induced Ca 2+ signaling is supported by knockdown and knockout studies in several cell types (Wang et al, 2004;Vasudevan et al, 2009;Yu et al, 2011). To examine whether there are PIPKIc isoform-specific differences in Ca 2+ signaling in our mice, we used the ratiometric Fura-2 Ca 2+ indicator dye to monitor ATP-induced intracellular Ca 2+ release in WT and PIPKIc 2/2 fibroblasts.…”
Section: Agonist-induced Camentioning
confidence: 99%
See 1 more Smart Citation